Hubungan Terpaan Iklan Dan Persepsi Pada Daya Tarik Brand Ambassador Tokopedia Dengan Minat Menggunakan Tokopedia Sebagai Sarana Transaksi Belanja Daring - Tazkia Irsyad, Raihana; Setyabudi, Djoko; Manalu, S. Rouli (Interaksi Online, 2021)
This study aims to determine the correlation between advertising exposure, perceptions on the Attractiveness of Tokopedia’s Brand ambassador, and the Intention in Using Tokopedia as Online Shopping Transaction Platform. This research used Strong Advertising Theory and Source Attractiveness Theory. This study used a sample of 60 people who in age from 18 – 34 years old who had been exposed to Tokopedia advertisement and knew Tokopedia’s brand ambassador. This sample method used nonprobability sampling with accidental techniques. The results showed advertising exposure with the intention in using Tokopedia had a significance value of 0.071 which means there is no significant correlation. Meanwhile, the perception of the attractiveness of Tokopedia brand ambassador and the intention in using Tokopedia has a significant value of 0.000, which means there is a significant correlation. The correlation coefficient is 0.468, which means it has a moderate and positive level of correlation.